Chicken soup for the college soul inspiring and humorous stories about college - Canfield, Jack 1944-. (Deerfield Beach, Fla. Health Communications, 1999)
"With stories by Robert Fulghum, Dave Barry, Katherine D. Ortega, George Plimpton, Will Keim, Eric Saperston."
6. Acts of kindness -- The boy under the tree / David Coleman and Kevin Randall -- For the kids / Diana Breclaw -- Piano music / Daneen Kaufman -- Ten-dollar bills and roses / Mary J. Davis -- A not-so-random act of kindness / Will Keim -- Christy's last day / Christy Calchera, as told to Dan Clark -- The gift of music / Brandon Lagana -- Our community / Christa F. Sandelier -- 7. Friends -- The kids in the hall / Suzanna Casamento -- My sanctuary / Eric Linder -- My friend Kim / Robert Tate Miller -- 819 Gaffield Place / Michele Bender -- An unlikely hero / Tony Luna -- With help from a friend / Dorri Olds -- 8. Tough stuff -- My star / Zan Gaudioso -- Independence Day / Natasha Carrie Cohen -- #38 Chucky Mullins / James Simmons -- Zap the Sap! / Eric Saperston -- I said no / Natasha Carrie Cohen -- The rest of the story / Jo Wiley Cornell -- Stuck with no way out / Rosanne Martorella -- 9. Mind over matter -- Breaking the mold / Zan Gaudioso -- A better message / Carol Grace Anderson -- Homeboy goes to Harvard / Richard Santana -- From the heart of a blessed temple / B.T. Thomas -- Second kind of mind / JeVon Thompson -- Work for your supper / Arlene Green -- Catsup soup / Cynthia Hamond -- Student super-saver / Kevin Van Gundy -- Dare to take risks! / Stephen Hopson -- Emma's ducks / Paul Karrer -- Consider this / Bill Clinton -- All in the family / Jeanne Marie Laskas -- Never too old to live your dream / Dan Clark -- 10. Graduation -- Life lessons / Dave Barry -- A homecoming of a different sort / Vicki Niebrugge -- Two stories for life / Robert Fulghum -- Humor them! / Katherine D. Ortega -- Know where you're going / Speaker's Sourcebook II -- Don't go / George Plimpton.
Keywords: College students -- Conduct of life